ChemInform Abstract: 2D 31P Solid State NMR Spectroscopy, Electronic Structure and Thermochemistry of PbP7. Issue 17 (April 2016) - Benndorf, Christopher; Hohmann, Andrea; Schmidt, Peer; Eckert, Hellmut; Johrendt, Dirk; Schaefer, Konrad; Poettgen, Rainer
Abstract: Phase pure polycrystalline PbP7 is prepared by solid state reaction of a 1:1 mixture of the elements using Pb as a flux (evacuated quartz tubes, 673 K, 6 d; 90—95% yield based on P).